STABILIZATION OF NEER IIB TYPE DISTAL CLAVICLE FRACTURE USING THE TIGHTROPE SYSTEM – CASE REPORT - Aleksandric, Dejan; Miceta, Lazar; Aleksic, Bojana; Dabetic, Uros; Grupkovic, Jovana (Srpski medicinski časopis Lekarske komore, 2023)
Introduction: Fractures of the distal end of the clavicle account for 10% – 30% of all fractures of this bone, however, they account for as many as 50% of non-unions and malunions in clavicle fractures. Of all distal clavicle fractures, the highest percentage of complications appertain to Neer type IIB fractures. The aim of this paper is to describe the case of a female patient with a Neer type IIB clavicle fracture treated by fracture reduction and flexible stabilization of the coracoclavicular joint using the TightRope system.Case report: A 48-year-old female patient, injured in a traffic accident while driving a car, suffered a Neer type IIB fracture of the distal edge of the left clavicle. Three days after the injury, the patient underwent indirect stabilization surgery of the coracoclavicular joint by fixation, with the application of the TightRope system. Rehabilitation began on the first postoperative day and was completed three months after surgery, with the achievement of full range of motion in the left shoulder, return of muscle tone and strength of the shoulder muscles, followed by a return to everyday life and work activities, as before the injury.Conclusion: Although no gold standard exists in the operative treatment of the above-described injuries, the indirect method of stabilization and flexible fixation of the coracoclavicular joint, using different types of sutures, achieves good to excellent results. Comparing this method with other described techniques indicates that it has a better functional result, which is achieved faster with a lower complication rate. Our patient's functional results contribute to literature data and yet again demonstrate the effectiveness of this type of treatment for these complex injuries.
Keywords: distal clavicle; fractures; internal fixation of fractures